Characterisation of key pests of amaranth and nightshades in Kenya and development of integrated pest management (IPM) strategies - Mureithi, Daniel Mwangi (My University, 2018)
Scanty information is available concerning the identity of the major pests of amaranth and African nightshades in Kenya and associated damage. The natural enemies of these pests have also not been studied in detail. In this PhD study, field survey to identify the major pests of amaranth and nightshades, their abundance, distribution, and damage in six regions in Kenya was conducted. The natural enemies for these pests present in the amaranth and nightshade fields in these regions were also profiled. Based on the survey findings, field experiments to study the population dynamics and host range for the major pests of African nightshades was done. The performance of parasitoid Aphidius colemani Viereck for the control of Aphis fabae Scopoli and Myzus persicae Sulzer was also tested. Finally, the biology of the nightshade veinal mottle virus (NsVMV) was investigated. Survey findings showed that the damage by insect from various insect orders on amaranth was; Lepidoptera- 24.41±1.39%, Homoptera- 16.61±1.15%, Coleoptera- 14.99±0.89%, and Thysanoptera- 4.06±0.63%. However, the most destructive insect species on amaranth were Spoladea recurvalis Fabricius, and Epicauta albovittata Gestro in the rainy and dry season respectively. Four important amaranth pests that had not been reported as pests of amaranth in Kenya i.e. Epicauta albovittata Gestro, Psara atritermina Hampson, Tuta absoluta Meyrick and Anyma octogueae Guenèe were also observed. In the survey for the African nightshade pests, the greatest damage was caused by Homopterans (26.8 %), Coleoptera (16.5%), Lepidoptera (5.1%) and Thysanoptera (3.7%). We observed 47 Coleoptera species, 6 aphid species, 8 Lepidoptera species and 8 Thysanoptera species infesting the African nightshades. However, A. fabae, and Epitrix silvicola Bryant were the two most damaging pests on the crop. Majority of the natural enemies observed belonged to the Coleoptera and Hymenoptera insect orders among them the parasitoid A. colemani which was studied during this PhD project. In the population dynamics study, we showed that highest abundance of A. fabae was observed in the 2nd growing season at the mid altitude zone and in the 3rd growing season in the high altitude zone. For the E. silvicola, the highest abundance was observed in the 4th growing season at the mid altitude zone and in the 3rd growing season at the high altitude zone. For the Lepidopteran pests (Spodoptera exigua, S. littoralis, Tuta absoluta and Plusia sp.), the peak abundance was recorded in the 1st growing season at the mid altitude zone and 4th growing season at the high altitude zone. For most of the pests, colonization on African nightshades started early at the seedling stage. However, the population rose and fluctuated at different ii phenological stages of crop growth. In the study of the performance of A. colemani, we showed for the first time that A. colemani has higher acceptance for M. persicae compared to A. fabae regardless whether the parasitoid was reared on S. scabrum or S. villosum as the host plants. However, higher parasitism was observed on A. fabae. Study on NsVMV revealed that Solanum lycopersicum, Nicotiana occidentalis, Nicotiana.hesperis, Nicotiana debneyi, Nicotiana tabacum cv. Samsun and Nicandra sp were the other hosts of the virus. There was no nightshade species/line resistant to the virus. In addition, 1000 seeds from NsVMV infected plants were germinated and found visually free from symptoms, indicating that the virus is if at all only to very low percentages seed-borne. Findings from the present study provide significant information necessary for designing and implementation of management interventions for the major pests of amaranth of African nightshades in Kenya.
Keywords: Amaranth pests; African nightshade pests; Pest biodiversity; Parasitoid; Plant viruses